(untitled) (Research, Society and Development, 2021)
Bariatric surgery is an alternative procedure to control obesity. It was included in the Unified Health System in 1999 and, even after twenty years, it does not meet the growing demand for care who accompanies the population’s changes in lifestyle. The present study aims to survey the number of bariatric patients performed by the Brazilian public system between 2010 and 2019, quantify the procedures by region, cost, complications and mortality rate; besides promoting critical vision in the academy. Using secondary data from the Hospital Information System of the Unified Health System, a quantitative and descriptive analysis of bariatric surgeries was performed within the targeted variables, analyzed through chi-square tests of independence and logistic regression. In ten years, there were 79,961 surgeries and invested R 49,186 million in bariatric. The distribution of surgeries in the Brazilian regions was not equal, with the south and southeast being the places that most performed procedures and received investments. The growth of surgery showed no statistical difference in the number of deaths, but the concomitant evident clinical and surgical complications with an increase of 266.66% and 800%, respectively. The most performed surgical technique was gastroplasty with intestinal bypass (94.15%), ranging within 4.7% observed. Although the number of surgeries has almost tripled within the period evaluated, it was not sufficient to supply the demand generated by the obesity epidemic, requiring equity in investments in this sector. Thus, there is an urgency to legitimate combat of this problem in Brasil, with effective public policies and health education.